(3HSJGf GdeYQaIs - (3GdMSjf Hf efUhQ GdMdGL, CHh eZjK,J (B309 (3g` s
(3ChdgG (B:s
(3bGd (B: (3GdMdGL bOS Gddg QhMg GdeYQaI ai Vef GdacQI aNajI hGdfcQI ai Vef GdeYQaI aNajI hGdfcQI UaI GdYGQa s
(3BNQgG (B:s
(3hGdfWb eY Cgd GdhShGS hGdacQI eY Cgd GdGjCS hGdZadI eY Cgd GdGSJjMGS hGdMb Mb hGdNdb Ndb JeJ GdHSJGf s
(3Vef eLehY , JQJjHgG (B: (3GdKGfis
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B260 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B63s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQVhjI (B- (3eTgO (B(381) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs